The Merck Index An Encyclopedia of Chemicals, Drugs, and Biologicals - O'Neil, Maryadele (MERCK COMPANY, 2006)
his is an edition of a standard reference for chemists, biochemists, pharmacists, and related professionals. It contains 10,000-plus monographs. About 4,000 of the entries cover drugs and pharmaceuticals, 2,000 describe common organic chemicals and laboratory reagents, another 2,000 cover naturally occurring substances and plants, 1,000 focus on the elements and on inorganic chemicals, and approximately 1,000 pertain to compounds of agricultural significance. Finally, several hundred discuss endogenous substances and biological agents. In addition to revisions and updating, changes include embedding the Chemical Abstracts Registry Numbers for title and derivative compounds within the monographs.